The educator's field guide : from organization to assessment (and everything in between) - Ebert, Edward S., 1953-; Ebert, Christine, 1946-; Bentley, Michael Lee. (Thousand Oaks, Calif. : Corwin, 2011)
'The Educator's Field Guide covers the four key areas of organization, classroom management, instruction, and assessment, and offers an excellent bridge from college to classroom'-- Provided by publisher.
'Targeted for pre-service and in-service teachers, this book is a guide to'what to do and how to do it in a very practical sense.' It addresses four essential topics: organizing and planning for instruction, classroom management, instructional techniques, and assessment. Each of the areas is addressed in a user-friendly, resource-style format, and includes activities and templates to provide readers with a framework for developing their own styles. Coverage of the four main topics is arranged in sub-topics that follow a five-step format of conceptualization, content, planning, implementation, and reflection'-- Provided by publisher.
Machine generated contents note: PrefaceUnit I. Instructional OrganizationBrief Outline for Unit IUnit I Concept MapUnit I Pep TalkFirst: Long Range Planning Why Plan Three Prerequisites Safety Demographics Content Area(s) Standards and AssessmentSecond Short Range Planning Unit Plans Goals and Objectives Lesson Plans Projects and Group WorkNow: Classroom Organization Student Seating Teacher's Seating Independent Work Areas Resource Storage/Availability Information Strategies for Moving From Place to Place Scheduling the Day in a Self-Contained ClassroomTomorrow: Instructional Presentation Use of the Primary Writing Surface Technology (The Old and the New)Finally: Communication with'Outsiders' School Staff Parents Museums, AgenciesConclusionUnit II. Classroom ManagementBrief Outline for Unit IIUnit II Concept MapUnit II Pep TalkFirst. Keys to Successful Classroom Management Management as the Basis for Effective Teaching The Basic Term Some Perspectives on Classroom ManagementSecond: Establishing a Management-Based Learning Environment Planning Communicating Expectations to the Students The Management Structure Teacher Behaviors Non-instructional TasksNow: Compiling Your Plan: A Template for Classroom ManagementWrite a Mission Statement Write Your Rules What Consequences will You Use? Discipline Program List Procedures for Your Classroom Ancillary Personnel Assessment of Your Classroom Management System ReflectionTomorrow: Implementing the Plan and Responding to Student Behavior A Signal Inform Practice ReinforceFinally: Assessing Your Classroom Management PlanUnit III. InstructionBrief Outline for Unit IIIUnit III Concept MapUnit III Pep TalkFirst: The Curriculum Defining'Curriculum' The Purpose of Curriculum You Actually Have Four Curriculums Perspectives of CurriculumSecond: The Student Cultural Influences and Ethnicity Reading Ability and Learning Styles Students with Exceptionalities Visual and Auditory Challenges Social Influences on DiversityNow: Conceptualizing Your Role Bringing the World to Your Students Instructional Techniques Monitoring and FlexibilityTomorrow: Putting it All Together Modeling Questioning Listening Demonstrating, Directing, and OrchestratingFinally: This is a People Profession Preparation, Preparation, Preparation Take Time to Enjoy Your ProfessionUnit IV. AssessmentBrief Outline for Unit IVUnit IV Concept MapUnit IV Pep TalkFirst: The Basics of Assessment The Basic Terms Standardized and Classroom AssessmentSecond: Making Assessment a Part of Instruction Foundation Ideas Questions to Ask of Any TestNow: Writing Tests The Table of Specifications: The Most Important Lesson Guidelines for Writing Test Items SummaryTomorrow: Analyzing the Results of Your Assessment Reviewing the Summary Statistics Item Analysis SummaryFinally: Assessment and the High-Stakes Environment Teaching, but not to the Test How Classroom Assessment Makes your Life EasierGlossaryReferencesIndex.
Machine generated contents note: PrefaceUnit I. Instructional OrganizationBrief Outline for Unit IUnit I Concept MapUnit I Pep TalkFirst: Long Range Planning Why Plan Three Prerequisites Safety Demographics Content Area(s) Standards and AssessmentSecond Short Range Planning Unit Plans Goals and Objectives Lesson Plans Projects and Group WorkNow: Classroom Organization Student Seating Teacher's Seating Independent Work Areas Resource Storage/Availability Information Strategies for Moving From Place to Place Scheduling the Day in a Self-Contained ClassroomTomorrow: Instructional Presentation Use of the Primary Writing Surface Technology (The Old and the New)Finally: Communication with'Outsiders' School Staff Parents Museums, AgenciesConclusionUnit II. Classroom ManagementBrief Outline for Unit IIUnit II Concept MapUnit II Pep TalkFirst. Keys to Successful Classroom Management Management as the Basis for Effective Teaching The Basic Term Some Perspectives on Classroom ManagementSecond: Establishing a Management-Based Learning Environment Planning Communicating Expectations to the Students The Management Structure Teacher Behaviors Non-instructional TasksNow: Compiling Your Plan: A Template for Classroom ManagementWrite a Mission Statement Write Your Rules What Consequences will You Use? Discipline Program List Procedures for Your Classroom Ancillary Personnel Assessment of Your Classroom Management System ReflectionTomorrow: Implementing the Plan and Responding to Student Behavior A Signal Inform Practice ReinforceFinally: Assessing Your Classroom Management PlanUnit III. InstructionBrief Outline for Unit IIIUnit III Concept MapUnit III Pep TalkFirst: The Curriculum Defining'Curriculum' The Purpose of Curriculum You Actually Have Four Curriculums Perspectives of CurriculumSecond: The Student Cultural Influences and Ethnicity Reading Ability and Learning Styles Students with Exceptionalities Visual and Auditory Challenges Social Influences on DiversityNow: Conceptualizing Your Role Bringing the World to Your Students Instructional Techniques Monitoring and FlexibilityTomorrow: Putting it All Together Modeling Questioning Listening Demonstrating, Directing, and OrchestratingFinally: This is a People Profession Preparation, Preparation, Preparation Take Time to Enjoy Your ProfessionUnit IV. AssessmentBrief Outline for Unit IVUnit IV Concept MapUnit IV Pep TalkFirst: The Basics of Assessment The Basic Terms Standardized and Classroom AssessmentSecond: Making Assessment a Part of Instruction Foundation Ideas Questions to Ask of Any TestNow: Writing Tests The Table of Specifications: The Most Important Lesson Guidelines for Writing Test Items SummaryTomorrow: Analyzing the Results of Your Assessment Reviewing the Summary Statistics Item Analysis SummaryFinally: Assessment and the High-Stakes Environment Teaching, but not to the Test How Classroom Assessment Makes your Life EasierGlossaryReferencesIndex.
Includes bibliographical references and index.
Keywords: Teaching -- Handbooks, manuals, etc